Performance Analysis of Novel Lightweight Photovoltaic Curtain Wall Modules Under Different Climatic Conditions - Guofeng Tao; Qunzhi Zhu; Yonggang Chen; Xiaolong Shi; Jun Guan (Energies)
Due to limited roof area, photovoltaic (PV) has gradually been installed on other facades of buildings. This research investigates the practical application of a lightweight PV curtain wall. We use EnergyPlus to build a base office building model of fit with a lightweight PV curtain wall. The performance of two typical lightweight PV curtain wall modules is evaluated in five sample Chinese cities of different climates. Simulations were carried out to determine the power generation of faux architectural material PV curtain wall modules (FAM PVCWMs) for the best cavity distance per facade in various cities. We discovered that, in Harbin, Beijing, and Shanghai, the capacity of PV curtain wall modules installed on the south facade is the best, while in Chengdu and Guangzhou, it is the west facade. We also analyzed the power generation and the impact on the indoor environment when installing semi-transparent PV curtain wall modules (ST PVCWMs). Compared with glass, the ST PVCWM’s power generation increased by at least 50%, while the glare index setpoint exceeded time reduced by at least 30.19%. Furthermore, when installed on the north facade of Chengdu and similar cities, it can ensure more than 50% of daylight indexed time and create a more favorable indoor environment.